1992
DOI: 10.1111/j.1365-2125.1992.tb04012.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of ageing on the stereochemical disposition of propranolol.

Abstract: The elderly are more resistant to the effects of propranolol than the young. To determine whether the decreased sensitivity in the elderly could be due to stereoselective alteration in propranolol metabolism, we investigated the effect of age on the oral clearance of (-)-and (+)-propranolol. Six young (aged 24-32, mean 27.3 ± 1.3 years) and six elderly (65-80, mean 71.3 ± 2.7 years) white male volunteers were given a single 80 mg oral dose of racemic propranolol. The mean peak plasma concentrations of both (+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Such is the case with calcium antagonists [69]. Thiazide diuretics, ACE inhibitors and some ß-blockers in the elderly should be adjusted according to renal function rather than age [70,71]. These features are summarized in table 1.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Such is the case with calcium antagonists [69]. Thiazide diuretics, ACE inhibitors and some ß-blockers in the elderly should be adjusted according to renal function rather than age [70,71]. These features are summarized in table 1.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…The two enantiomers appear to be equally potent as a,-blockers, but the P-blockade is principally attributable to the S( -)-enantiomer. l5 We have previously found that the nonselective P-blocker propranolol, which is also given as a racemic mixture, is stereoselectively metabolized in humans, [16][17][18] and this stereoselective metabolism is dependent on CYP2D6. l6 If stereoselective metabolism of carvedilol occurs and if that stereoselective metabolism is CYP2D6 dependent, then one would predict that poor metabolizers of debrisoquin (8% of the U.S. population) may respond differently than rapid metabolizers to carvedilol administration.…”
mentioning
confidence: 99%
“…Examples include the effects of aging on the metabolism of drugs that are conjugated in the liver prior to excretion and the metabolism of drugs prescribed as racemic mixtures. In contrast, Zhou et al (1992) failed to find any age-related differences in the disposition of propranolol enantiomers. Similarly, a differential response in terms of S-(+) and R- (-) hexobarbital clearance following concurrent administration of rifampicin (rifampin) to young and elderly volunteers has been reported (Smith et al 1991).…”
Section: Future Needsmentioning
confidence: 68%